2016
DOI: 10.4103/2230-8210.180005
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and body mass index in polycystic ovary syndrome

Abstract: Objective:Polycystic ovary syndrome (PCOS) is a common endocrine disorder associated with obesity. Human and animal studies showed a direct relationship between leptin level and obesity, however, results from different studies were mixed. This study investigated the status of leptin level in PCOS and its relationship with body mass index (BMI) in a group of Iranian women with PCOS.Methods:In this cross-sectional study, 40 women with PCOS and 36 healthy women were assigned to experimental and control groups, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
4
23
0
2
Order By: Relevance
“…In fact, Montazerifar et al indicated that Leptin levels were significantly higher in abdominal obese patients than those in patients without abdominal obesity or in the control group. This result was partly consistent with earlier reports …”
Section: Discussionsupporting
confidence: 94%
“…In fact, Montazerifar et al indicated that Leptin levels were significantly higher in abdominal obese patients than those in patients without abdominal obesity or in the control group. This result was partly consistent with earlier reports …”
Section: Discussionsupporting
confidence: 94%
“…101 Upregulation of adipokine mRNA in peripheral adipose tissues has been associated with PCOS, obesity, and hyperinsulinemia. 102 , 103 Future directions for our studies could investigate the synthesis and release of androgens and adipokines into circulation and determine whether this also contributes to hyperandrogenemia or increased risks of cardiovascular disease in women with PCOS and other disorders that fall under metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) has been considered the most common multifactorial endocrinopathy syndrome [ 1 , 2 ], which affects about 15% of reproductive age women [ 2 , 3 ]. It is a heterogeneous condition characterized by chronic anovulation, hyperandrogenism [ 4 , 5 ], and polycystic ovarian morphology [ 6 ].…”
Section: Introductionmentioning
confidence: 99%